Afghanistan students' perceptions of the use of online tools for enhancing learning - Mohammad Basir, Bakhtyari (2015)
Online tools play a significant role in higher education where it can be used to assist learning and teaching process. Several studies showed that online tools have the capacity to provide new learning environment and experiences for both teachers and students. There are many learning activities which can be facilitated by online tools such as collaborating, interacting, discussing, sharing, creating and exchanging ideas, information and knowledge. These activities are more student-centered, and can enhance students‟ learning and thinking skills. Online tools can enhance students‟ learning approach such as surface and deep approach to learning. Moreover, different level of thinking skills like lower and higher order thinking skills can also be improved when online tools are utilized. In Afghanistan, the Ministry of Higher Education, and other relevant studies indicated that the current learning and teaching approaches in Afghanistan which are rather conventional are not effective for today‟s students. They need to be revised. In order to move toward applying student-centered and technology-driven, the Ministry of Higher Education encourages all universities to use technology to assist teaching and learning. The purpose of the study was to investigate Afghanistan university students‟ perceptions on the use of online tools for learning and thinking skills. In addition, the purpose of the study was to find out the barriers of using online tools in learning. Hence, the mixed method research design was employed to collect both qualitative and quantitative data for the study. Researcher developed survey questionnaire and semi-structured interview were the research instruments. The questionnaire was distributed to 217 tertiary students of two public and private universities to measure their perceptions on the use of online tools for learning and thinking skills. Beside this, a semi-structured interview was conducted with 35 volunteered students to support the quantitative data. The results generally show positive perceptions of the effects of using online tools on both learning and thinking skills. The participants believed that utilizing online tools helped them improve their surface approach learning better than deep approach. The participants also believed that their lower-order thinking could enhance better by using online tools than higher order thinking skills. Moreover, they stated that there are the barriers faced by the universities of using online tools for learning. There are implications for the Ministry of Higher Education, universities and educators.